Pajejiwan Dalam Upacara Mapeselang: Kajian Siwa-Budha - Ida Ayu Tary Puspa; Ida Bagus Subrahmaniam Saitya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The ceremony is part of the three frameworks of Hinduism. As part of the five sacrifices that are carried out sincerely, there is Dewa Yadnya. One of them is the mapeselang ceremony, a series of ngenteg linggih. What's unique about this procession is that there is a mlaspas in a holy place, mulang pedagingan, after that so that Ida Hyang Parama Wisesa can sit at the pelinggih, then mepeselang is carried out, namely pratima is lowered through a new buffalo caru to the bale peselang . Finally, they will also be picked up to the bale pedanan. When the procession is finished, there will be a religious dialogue between Pedanda Shiva-Buddha in which the conversation is about the contents of this universe. By holding this rite, it is hoped that the harmony of the cosmos will occur through creation, maintenance, and annihilation.